Insight into the evolution and functional characteristics of the pan‐genome assembly from sesame landraces and modern cultivars. Issue 5 (8th December 2018) - Yu, Jingyin; Golicz, Agnieszka A.; Lu, Kun; Dossa, Komivi; Zhang, Yanxin; Chen, Jinfeng; Wang, Linhai; You, Jun; Fan, Dingding; Edwards, David; Zhang, Xiurong
Summary: Sesame ( Sesamum indicum L.) is an important oil crop renowned for its high oil content and quality. Recently, genome assemblies for five sesame varieties including two landraces ( S. indicum cv. Baizhima and Mishuozhima) and three modern cultivars ( S. indicum var. Zhongzhi13, Yuzhi11 and Swetha), have become available providing a rich resource for comparative genomic analyses and gene discovery. Here, we employed a reference‐assisted assembly approach to improve the draft assemblies of four of the sesame varieties. We then constructed a sesame pan‐genome of 554.05 Mb. The pan‐genome contained 26 472 orthologous gene clusters; 15 409 (58.21%) of them were core (present across all five sesame genomes), whereas the remaining 41.79% (11 063) clusters and the 15 890 variety‐specific genes were dispensable. Comparisons between varieties suggest that modern cultivars from China and India display significant genomic variation. The gene families unique to the sesame modern cultivars contain genes mainly related to yield and quality, while those unique to the landraces contain genes involved in environmental adaptation. Comparative evolutionary analysis indicates that several genes involved in plant‐pathogen interaction and lipid metabolism are under positive selection, which may be associated with sesame environmental adaption and selection for high seed oil content. This study of the sesame pan‐genome provides insights into the evolution and genomic characteristics of this important oilseed and constitutes a resource for further sesame crop improvement.